Ecohydrological and vegetational changes in a restored bog and fen - Jauhiainen, Sinikka; Laiho, Raija; Vasander, Harri (2006)
The vegetation of two boreal mires drained for forestry was studied prior to and after restoration (removal of tree stand and filling in of ditches). The restoration induced a rapid rise in the water table level and caused relatively rapid changes in plant species composition and cover. On the minerotrophic fen site, the number of forest species declined and the cover of Eriophorum vaginatum increased five-fold, reaching over 50% cover in three years. On the ombrotrophic bog site, the terrestrial lichens disappeared, while the cover of Empetrum nigrum, Calluna vulgaris, E. vaginatum, and Sphagnum balticum increased. Changes in water table level and vegetation indicate a change towards a functional mire ecosystem.